RELIABILITAS DAN KEUNIKAN INJIL SINOPTIK - Johan Johan; Ni Nyoman Fransiska (Jurnal Penggerak, 2024)
The Synoptic Gospels are very interesting books because they have the same story about the person of Jesus Christ. And it's even more interesting because the story of Jesus is told with the same story. There's almost no difference. This is meant because each Gospel writer has a different intention and also addresses it differently. This writing uses qualitative methods using library research methods, namely using the Bible, dictionaries, commentaries and journals, which relate to discussions in the author's scientific work. Researchers also use an exegetical approach through the application of hermeneutic principles and methods. Thus, the research results found that the synoptic gospels were written for different addresses and purposes according to the situation of the congregation. And this gospel also conveys God's will for His people in the church today.